TRAINING OF FUTURE ENERGY SPECIALISTS TO SOLVE PRACTICAL PROBLEMS ON THE BASIS OF PHYSICAL PROJECTS - Sosnickaya, Natalya; Kryvylova, Olena (Physical and Mathematical Education, 2021)
Formulation of the problem. In the field of higher education, general and special competencies are acquired, which have in common the ability to apply knowledge in practical situations. Therefore, the formation of mental and practical skills and abilities of future energy specialists to solve practical problems is becoming more and more important. The effectiveness of solving practical problems in the field of power engineering, electrical engineering and electromechanics depends on the understanding by future specialists of energy profile the theories and methods of physics. There is a need to develop and implement effective teaching methods, in particular on the basis of physical projects.Materials and methods. The analysis of research in the field of education, the National Qualifications Framework, the standard of higher education in the specialty 141 "Electricity, Electrical Engineering and Electromechanics" for the first (bachelor's) level of higher education to theoretically substantiate the requirements for mental and practical skills of future energy specialists to solving practical tasks and advantages of physical projects in their formation was carried out; pedagogical experiment was carried out for testing the effectiveness of the use of physical projects in the training of future energy specialists; diagnostics (using the 16-factor personal questionnaire of R. Cattell and the method of analysis of products of activity as projects) was for evaluation the levels of ability of future energy specialists to solve practical problems using theories and methods of physics; statistical calculations, such as quantitative and qualitative data processing, graphical presentation of results, were for tracking the dynamics of the levels of formation of the ability of future energy specialists to solve practical problems and establishing the scientific reliability of the results of the study.Results. The essence of physical projects and features of their using are theoretically substantiated on the example of discipline "Alternative energy", the maintenance of which is directed on formation of ability to apply the received theoretical knowledge, scientific and technical methods for the decision of scientific and technical problems and problems of power.Such criteria as personal, content-procedural, evaluation-regulatory, indicators and diagnostic tools for testing the ability of future energy specialists to solve practical problems with the using of physics methods are characterized.The analysis of experimental data showed significant qualitative changes in the levels of formation of the ability of future energy specialists to solve practical problems by EG physics. That is confirmed by calculations of Pearson's criterion (17,61> 7,8).
Keywords: energy specialists; practical problems; physical project; competence; pedagogical experiment